Potential applications of ionic liquids in ecologic wood processing - Patachia, Silvia; Croitoru, Catalin (Pro Ligno, 2013)
In this paper, the influence of four types of imidazolium chlorides ionic liquids on the surface properties of wood (Populus sp.) veneers has been studied by using contact angle and electrical conductivity analysis. The measurements showed that wood wettability is increased by ionic liquid treatment, thus enabling a higher compatibility of wood with polar additives or adhesives. The electrical conductivities of treated wood by the method presented in this paper are in the 0.8-1.65mS/cm ranges, higher than the ones reported in the reference literature, which confers the treated wood anti-electrostatic properties.
Keywords: wood veneers; ionic liquids; surface energy; anti-electrostatic materials.